PENGARUH WAKTU REAKSI ETANOLISIS PADA SUHU RUANG TERHADAP RENDEMEN DAN STABILITAS EMULSI PRODUK ETANOLISIS Palm Kernel Oil (PKO) [The Effect of Ethanolisis Reaction Time at Room Temperature on Yield and Emulsion Stability Ofproduct of Ethanolisis Palm Kernel Oil (PKO)] - Yunggo, Jessica; murhadi, murhadi; Hidayati, Sri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
PKO (palm kernel oil) is made from palm kernel of Elaesis gueneensis Jacq, which is a mixture of triglycerides. Triglycerides can be converted into a number of derivative products such as mono-diglycerides (MG-DG). MG-DG can be formed by ethanolisis reaction. In this study ethanolisis reaction of PKO was done by adding 96% of technical ethanol containing NaOH 1% (w/w PKO) on PKO solution at a room temperature and a shorter time than the another PKO ethanolisis before. This study was aimed to find the best PKO ethanolisis reaction time in providing products of ethanolisis PKO with yield and high emulsion stability. The experiment was a nonfactorial and arranged in a complete randomized block design (CRBD) with four replications. The single factor studied was 7 levels of the reaction time in which were 1, 3, 5, 7, 9, 11 and 13 minutes. The data were analysed using ANOVA and further by Orthogonal polynomial on the significant level of 1% and 5%. The results showed that the reaction time ethanolisis had no effect on the yield and stability of the emulsion of fresh coconut milk. The yield of the resulting range between 17.32% - 18.07% and the stability of emulsion ranged between 88.88% - 92.50% during one day and 85.23% - 89.50% during two days. The sensory observation indicated that PKO ethanolisis product can preserve coconut milk for 3 days of storage time with color and scent of fresh coconut milk, and more stable compared to control.Keywords: emulsion stability, ethanolisis, PKO, time, yield